Literacy Based Behavioral Interventions and Video Self-Modeling with students with Autism Spectrum Disorder (ASD) - Leach, Debra; Rodecki, Jennifer (Journal of the American Academy of Special Education Professionals, 2013)
Educators are continually seeking effective, research-based strategies to address the unique needs of their students with autism spectrum disorders (ASD). It is well documented that students with ASD benefit from direct instruction and visual supports when learning new skills. This article provides step-by-step procedures for using a tiered intervention package consisting of literacy-based behavioral interventions and video-self modeling to teach new skills to students with ASD to promote mastery and independence. Authors share an action research process that was used to identify a need for students with ASD in a middle school classroom, select and implement research-supported interventions to address the need, and to monitor progress throughout the phases of intervention to make instructional decisions.